Kazakhstan's foreign policy strategy within the framework of Central Asian integration - Zhunissov, Zhassulan; Uderbaeva, Bakhyt; Kurmangali, Medeu; Darkenbayev, Askat; Tazhikov, Abzal (Asian journal of political science, 2025)
This study analyzes the evolution of Kazakhstan's foreign policy strategy in relation to regional integration initiatives in Central Asia and the influence of global power to it. The geopolitical space of Central Asia, also known as Turkestan, consists of Kazakhstan, Uzbekistan, Kyrgyzstan, Turkmenistan, and Tajikistan. Using historical, institutional, and value-normative approaches, this article examines the development of Kazakhstan's strategy after independence through its participation in multilateral frameworks like the Central Asian Union, CACO, SCO, as well as bilateral partnerships. The key trend identified is a shift from reliance on multilateral mechanisms to prioritizing bilateral relations within the region, driven by pragmatism and economic considerations. However, persisting challenges like regional instability may require Kazakhstan to reengage in multilateral cooperation on shared issues. By mapping Kazakhstan's changing strategy, this study provides useful insights into a secondary power's navigation of major power interests while seeking greater leadership in its region. It contributes to scholarship on Central Asian cooperation and the foreign policy options of states in this area. The analysis will interest researchers in regional studies, ethnography, and comparative politics, as well as general readers interested in Kazakhstan's evolving strategic priorities.